Health Promotion and Sexology Student and Teaching Staff Perspectives of Online Learning and Teaching During COVID-19: A Mixed Methods Study. (June 2022) - Blackford, Krysten; Birney, Kieran; Sharma, Shefali; Crawford, Gemma; Tilley, Matt; Winter, Sam; Hendriks, Jacqueline
Universities are undergoing rapid and unprecedented changes due to the COVID-19 pandemic, and the needs of learners during this transition are not necessarily well understood or addressed. This study aimed to examine the impact of the "remote internal" unit delivery in a large Western Australian university, as experienced by students and teaching staff within a department of health promotion and sexology (DHPS). In the remote internal mode, previously "internal" (face-to-face) students received prerecorded lectures and attended workshops and seminars in real time through use of the learning platforms. The mixed methods study was conducted across three phases in 2020. A quantitative online student survey was followed by student and teaching staff focus groups and document analysis. Six themes were uncovered regarding the student experience of the remote internal mode: (1) face-to-face contact provides a sense of community, (2) online learning is better when it is interactive, (3) online learning is convenient, (4) delivery mode affects student willingness to contribute to discussions, (5) students enjoy a mixture of teaching patterns, and (6) technological issues create barriers to effective learning. Five themes were revealed regarding teaching staff experience of the remote internal mode: (1) connections matter, (2) face-to-face delivery enhances engagement, (3) learning outcomes are a priority for teaching staff, (4) online delivery needs effective supports, and (5) students have online privacy concerns. Considerations for course modalities, methods to enhance interactivity, and supportive technology and infrastructure are recommended to ensure that the technological, demographic, and socio-environmental needs of students are adequately met.